2011
DOI: 10.1523/jneurosci.5199-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Controlled Alpha Band Activity in Somatosensory Areas Determines Behavioral Performance in a Discrimination Task

Abstract: The brain receives a rich flow of information which must be processed according to behavioral relevance. How is the state of the sensory system adjusted to up-or downregulate processing according to anticipation? We used magnetoencephalography to investigate whether prestimulus alpha band activity (8 -14 Hz) reflects allocation of attentional resources in the human somatosensory system. Subjects performed a tactile discrimination task where a visual cue directed attention to their right or left hand. The stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
399
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(455 citation statements)
references
References 31 publications
(49 reference statements)
52
399
4
Order By: Relevance
“…We found that decreases in α-activity during the decision period correlated with task performance in S1, S2, DPC, MPC-left, and M1. The current findings are consistent with previous work showing that somatosensory α-activity influences discrimination performance (18,27) and with the visuospatial attention literature linking α-activity to detection performance (15)(16)(17). These previous findings have resulted in the notion that α-activity is involved in sensory gating.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that decreases in α-activity during the decision period correlated with task performance in S1, S2, DPC, MPC-left, and M1. The current findings are consistent with previous work showing that somatosensory α-activity influences discrimination performance (18,27) and with the visuospatial attention literature linking α-activity to detection performance (15)(16)(17). These previous findings have resulted in the notion that α-activity is involved in sensory gating.…”
Section: Discussionsupporting
confidence: 92%
“…In support of this idea, several studies on visual perception have shown that anticipatory α-activity reflects the orienting of attention (9)(10)(11)(12)(13)(14) and influences detection performance (15)(16)(17). Recently, it was shown that the functionality of α-oscillations can be generalized to the somatosensory system (18)(19)(20)(21). Furthermore, α-activity has been implicated in visual (22)(23)(24)(25), auditory (26), and somatosensory working-memory performance (27).…”
mentioning
confidence: 88%
“…We found a similar negative relationship between alpha and reporting of touch over ipsilateral somatosensory cortex on touch absent trials as we found over contralateral cortex. Alpha over sensory regions other than the primary region associated with a task may play a key role in suppressing irrelevant information -the gating-by-inhibition hypothesis -as seen in a number of studies of spatial attention (Gray, Frey, Wilson, & Foxe, 2015;Haegens et al, 2011Haegens et al, , 2011Jensen & Mazaheri, 2010). Thus, when attending to the right hand, alpha power increases over right, ipsilateral somatosensory cortices and decreases over left, contralateral somatosensory cortices.…”
Section: Discussionmentioning
confidence: 98%
“…Alpha oscillations may thus reflect pulses of cortical inhibition (Mathewson et al, 2011), as a sensory region adjusts to temporal expectations of the delivery of a stimulus by ensuring it is in high-excitability state when a stimulus is expected. Top-down manipulation of alpha power may also be a mechanism for the suppression of irrelevant stimuli (Haegens, Händel, & Jensen, 2011), through the inhibition of cortical regions dealing with, for example, unattended regions of space. This may also be used to gate communication between different cortical regions (Jensen, Bonnefond, & VanRullen, 2012;Jensen & Mazaheri, 2010), allowing or preventing early sensory responses to reach consciousness (Weisz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this manipulation was to control for the effects of expectancy during the task, which has been shown to modulate the activity of cortical sensorimotor areas [thereby affecting response times; e.g. Haegens et al (2011)]. Moreover, recent investigations in our lab have revealed that the optimal ratio of real to catch trials in this paradigm is 1:1 (Kandula et al 2017).…”
Section: Visuotactile-interaction Taskmentioning
confidence: 99%